OPTIMASI AKTIVATOR DALAM PEMBUATAN KOMPOS ORGANIK DARI LIMBAH KAKAO - Yanqoritha, Nyimas (MEKTEK, 2013)
The purpose of the study is to determine the ability of the composting process composting time to examine theÂ relationship to temperature, pH and levels of C, N, Ratio C / N, P using EM4 activator, MOD 71, sheep dungon cocoa waste biomass. The working principle of the study is to observe and analyze the decomposition ofbiomass wastes cocoa to different activators and observe the process of composting process variables for 7,14, 21, 28, 35, 42, 49, and 56 days with the analysis of temperature, pH and analyze levels of nitrogen (N),Carbon (C), Ratio C / N, and phosphorus (P). Results were obtained in accordance with the optimizationpoint of the graph N, C, Ratio C / N, and P. Then connected to the SNI table, suitable compost is compostactivator biomass using EM4, at 28 days with temperatures 54.88 0C and compost maturation is the 56dayof temperature 28 Â° C with a pH of 7.46.Keywords: Biomass, activator, EM4, MOD 71